Malignant Ependymoblastoma Mimicking a Benign Pilocytic Astrocytoma - Thong, Pham Minh (Neurol Int, 2020)
Ependymoblastoma is an uncommon, exceedingly malignant brain neoplasm that adversely influences children’s quality of life. Ependymoblastoma represents a subtype of primitive neuroectodermal tumors, categorized as grade IV, according to the 2007 World Health Organization (WHO) classification of central nervous system tumors. Ependymoblastomas are often located in the supratentorial zone and often associated with the ventricular system. Histopathological sections of the tumor revealed uniform, primitive, small blue cells, with multi-layered rosettes, accompanied by abundant mitoses. The clinical and imaging features of ependymoblastomas are not specific, which can result in misdiagnosis as other brain neoplasms. In this paper, we described the identification of a fourth-ventricular ependymoblastoma that was misdiagnosed as pilocytic astrocytoma, despite the utilization of advanced magnetic resonance imaging (MRI) protocols.